Energy - Elliott, Deborah (Wayland, Hove, 1993)
"Energy" by Deborah Bedford Elliott, published in 1993, is part of the "Into Europe" series. This 48-page book examines various types and uses of energy across Europe, discussing the importance of energy conservation and evaluating the advantages and disadvantages of different energy sources. It is illustrated in color throughout.